The Influence of Sustainable Tourism Certification, Local Community Awareness, and Product Innovation on the Reputation of Destinations in Yogyakarta - Akbarina, Farida; Widyaningsih, Heni; Sugito, Ery; Mardiah, Ainil; Fitrianingrum, Rini (West Science Social and Humanities Studies, 2024)
This study examines the influence of sustainable tourism certification, local community awareness, and product innovation on the destination reputation of Yogyakarta, Indonesia. Using a quantitative approach, data were collected from 270 respondents representing tourists, local residents, and tourism service providers, and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that all three factors significantly and positively impact Yogyakarta’s destination reputation. Sustainable tourism certification enhances the image of the destination, while local community awareness fosters support for sustainable practices. Additionally, product innovation contributes to the competitiveness and attractiveness of Yogyakarta by offering unique and sustainable tourism experiences. These findings highlight the importance of integrating sustainability, community engagement, and innovation to build and maintain a strong destination reputation. Practical implications for tourism stakeholders and policymakers in Yogyakarta are discussed.